Biophilic design features in vernacular architecture and settlements of the Naxi - Li, Mengbi; Chau, Hing-Wah; Aye, Lu (Journal of Architecture and Urbanism, 2020)
As a newly formed concept, “Biophilic design” is attracting a growing attention among both practitioners and academics. However, the link between biophilic design and vernacular architecture has yet to be thoroughly explored, especially in the context of China, which is the gap this article aims to fill. Investigating the vernacular architecture of the Naxi, this research found that biophilic design attributes and features existed in vernacular buildings and settlements. A matrix framework was developed to facilitate the in-depth investigation of the interrelated elements of the Naxi such as local climate, topography, culture, their belief system, conventions, arts and literature. Among other results, we found that the local culture was influenced by animism and distinct cosmic models. Also, the buildings were constructed using the traditional ways of material preparation and conventions of occupancy. This research serves as an important springboard to bridge between studies in biophilic design and studies in vernacular architecture and settlements.